2010
DOI: 10.1186/1471-2474-11-97
|View full text |Cite
|
Sign up to set email alerts
|

Primary hemiarthroplasty versus conservative treatment for comminuted fractures of the proximal humerus in the elderly (ProCon): A Multicenter Randomized Controlled trial

Abstract: BackgroundFractures of the proximal humerus are associated with a profound temporary and sometimes permanent, impairment of function and quality of life. The treatment of comminuted fractures of the proximal humerus like selected three-or four-part fractures and split fractures of the humeral head is a demanding and unresolved problem, especially in the elderly. Locking plates appear to offer improved fixation; however, screw cut-out rates ranges due to fracture collapse are high. As this may lead to higher ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
0
30
0
2
Order By: Relevance
“…High rates of osteonecrosis and fracture collapse have led some authors to advocate for hemiarthroplasty as the treatment of choice for Bat-risk^fractures [17]. However, the range of motion after hemiarthroplasty is highly variable, and two studies have reported no functional difference between hemiarthroplasty and nonsurgical treatment [18].…”
Section: Discussionmentioning
confidence: 98%
“…High rates of osteonecrosis and fracture collapse have led some authors to advocate for hemiarthroplasty as the treatment of choice for Bat-risk^fractures [17]. However, the range of motion after hemiarthroplasty is highly variable, and two studies have reported no functional difference between hemiarthroplasty and nonsurgical treatment [18].…”
Section: Discussionmentioning
confidence: 98%
“…High rates of ON and fracture collapse have led some authors to advocate for hemiarthroplasty as the treatment of choice for ''at-risk'' fractures [21]. However, motion after hemiarthroplasty is highly variable and two reports found no functional difference between hemiarthroplasty and nonoperative treatment [6,31]. Internal fixation can produce better functional outcomes than hemiarthroplasty [28], particularly when complications are avoided [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis of the injury, as well as consideration of the patient's preinjury function and needs, will allow for acceptable outcomes for most patients. 83,93 Treatment of the proximal humerus fracture is complex and should be uniquely designed to provide for the best functional outcome for each patient.…”
Section: Nonhip Fractures Proximal Humerus Fractures (H Hoyen and Smentioning
confidence: 99%